Softening the Blow of Social Exclusion: The Responsive Theory of Social Exclusion - Freedman, Gili; Williams, Kipling D.; Beer, Jennifer S. (Frontiers in Psychology, 2016)
Social exclusion is an interactive process between multiple people, yet previous research has focused almost solely on the negative impacts on targets. What advice is there for people on the other side (i.e., sources) who want to minimize its negative impact and preserve their own reputation? To provide an impetus for research on the interactive nature of exclusion, we propose the Responsive Theory of Social Exclusion. Our theory postulates that targets and sources’ needs are better maintained if sources use clear, explicit verbal communication. We propose that sources have three options: explicit rejection (clearly stating no), ostracism (ignoring), and ambiguous rejection (being unclear). Drawing on psychology, sociology, communications, and business research, we propose that when sources use explicit rejection, targets’ feelings will be less hurt, their needs will be better protected, and sources will experience less backlash and emotional toil than if sources use ambiguous rejection or ostracism. Finally, we propose how the language of rejections may impact both parties.